Síndrome de Parry Romberg: uma abordagem multidisciplinar - Castro, Laura Maria dos Santos Reis Rocha de (2019)
INTRODUCTION: Parry Romberg syndrome (PRS) is a rare, slow and progressive degenerative condition that affects skin, subcutaneous tissue, muscles and bones of the face. Hemifacial atrophy and consequent asymmetry are its main characteristics. Although the etiology of PRS is not defined, the condition seems to be related to autoimmune reactions, infections, heredity, endocrine disorders and trauma. In general, the condition manifests itself between the first and second decades of life, progressing for a few years until it reaches a steady state. The diagnosis is made through signs and symptoms observed during the clinical evaluation, combined with the patient's history and specific tests. Therapy includes from orthodontic/prosthetic/ ophthalmologic therapies to the restitution of lost tissue with plastic surgery and, more recently, with intradermal fillers. PURPOSE: To report a case of Parry Romberg syndrome with a focus on the multidisciplinary approach. CASE REPORT: A 24-yearold female patient attended the Clinic-School of Dentistry of the Federal University of Sergipe, campus of Lagarto, complaining of pain in the temporomandibular joint. Based on the clinical findings, among them hemifacial atrophy on the left side, alopecia in the scalp, muscular spasms in the submandibular and left temporal region, besides enophthalmia in the corresponding side, the patient was diagnosed with ParryRomberg Syndrome. Therapy had as its primary objective the relief of symptoms through referral to physiotherapy. Subsequently, rehabilitation dental treatment was started, significantly assisting in the resolution of the main complaint presented. CONCLUSION: Health professionals should be able to establish the diagnosis of SPR from the characteristics visualized during the initial examination. The establishment of adequate therapy is imperative to provide improvements in the patient's quality of life. The conduction of the case must be done by a multiprofessional team, considering the involvement of the different structures of the body.